Mapping the research trends on the biological effects of radiation less than 100 mSv: a bibliometric analysis for 30 years publication. (1st May 2019) - Park, Jina; Kwon, TaeWoo; Lee, Seung-Sook; Jin, Young Woo; Seong, Ki Moon
Abstract: Purpose: The purpose of this study is to evaluate the global scientific publication of biological research of low dose radiation for the past 30 years and provide the insights into the characteristics of research activities and major topics regarding biological effects of low dose radiation exposure. Materials and methods: We bibliometrically investigated the biological research publication of radiation exposure less than 100 mSv. References published from 1987 to 2016 were achieved from the Scopus database and filtered by several criteria such as publication types, research fields, and radiation dose range. Results: Total 753 references were assembled for the bibliometric analysis on the biological studies of radiation effect less than 100 mSv. It provided fundamental knowledge of research, including production tendency, contribution, impact journals, and major research themes. Based on the keyword analysis, we found that specific topics on the biological response to radiation exposure have been changed from the examination of low dose radiation-induced phenomena to the investigation of how to induce a physiological response. In addition, featured articles showed the various views on the biological effects of radiation less than 100 mSv in 30 years publication, depending on radiation doses and types. Conclusions: Continuous studies in large programs of low dose radiation led to the increment of research achievements in accordance with societal needs in radiation safety regulation for health protection. Our findings can surely help radiation researchers to gain insights and penetration in low dose risk research for radiation protection, and establish a further research direction.